2019
DOI: 10.3390/robotics8020028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Voltage Dips on Robotic Grasping

Abstract: This paper addresses the effects of electric power quality on robotic operations. A general overview is reported to highlight the main characteristics of electric power quality and it’s effects on a powered system by considering an end-user’s viewpoint. Then, the authors outline the influence of voltage dip effects by focusing on robotic grasping applications. A specific case study is reported, namely that of LARM Hand IV, a three-fingered robotic hand which has been designed and built at LARM in Cassino, Ital… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The quality of service, namely the Power Quality (PQ), is due to several types of disturbances, ranging from transients to variations [1][2][3]. Every disturbance can cause detrimental effects on the performance of the components of the power system as well as on the load machinery and equipment Among various disturbances, voltage sags stand out as one of the most critical challenges for industrial processes, especially in high-tech industries with great automation penetration and intensive usage of sophisticated equipment [4][5][6]. The forecast of the voltage sags number, that will happen at specific sites, was considered prohibitive in relevant literature until a few years ago.…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation
“…The quality of service, namely the Power Quality (PQ), is due to several types of disturbances, ranging from transients to variations [1][2][3]. Every disturbance can cause detrimental effects on the performance of the components of the power system as well as on the load machinery and equipment Among various disturbances, voltage sags stand out as one of the most critical challenges for industrial processes, especially in high-tech industries with great automation penetration and intensive usage of sophisticated equipment [4][5][6]. The forecast of the voltage sags number, that will happen at specific sites, was considered prohibitive in relevant literature until a few years ago.…”
Section:  mentioning
confidence: 99%
“…It's important to note that when it comes to the presence of clusters, the total sags do not exhibit the statistical characteristics of a Poisson distribution process, as observed for rare sags in Section C. In order to 4 If a cubic-square transformation is applied to handle the broad range of ttnek (from some seconds to 10 6 s), replaces the relation (4) characterize the random occurrence of ttne k over time, it is essential to employ a stochastic model for voltage sag events. As suggested in [16,20,21], when the sag rate decreases monotonically over time, the random variable ttne k representing the total sags at site k can be accurately described using a Gamma distribution: (5) where Γ represents the Gamma function, α k stands for the shape parameter, and β k is the scale parameter. The mean value of equation ( 5) can be expressed as equation ( 6): (6) To predict the total number of sags at a specific site denoted as k, we begin by calculating the mean value as described in equation ( 6).…”
Section: Steps 3b 4b 5b Of Path Bmentioning
confidence: 99%
“…In the first paper, the authors outline the influence of electric power quality on the performance of a robotic device. Namely, voltage dip effects are addressed from an experimental viewpoint by focusing on robotic grasping applications [11]. A specific case study is reported, by means of a three-fingered robotic hand.…”
Section: Advances In Italian Roboticsmentioning
confidence: 99%
“…as a result of voltage sags. There is a common phenomenon resulting from the differences in the classes of electromagnetic resistance between a robot and its equipment [7]. The authors of the article "Effects of Voltage Dips on Robotic Grasping" discuss the effects of disturbances in power quality on robot performance, with particular emphasis on the effects of voltage sags on the robot supply system and auxiliary equipment from the point of view of the end user/operator.…”
Section: Introductionmentioning
confidence: 99%